2008
DOI: 10.1007/s00228-008-0514-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing patterns and hospital admissions with respiratory and urinary tract infections

Abstract: Our findings show a statistically significant relationship-at the GPs level-between the quantitative antibiotic prescribing rate and standardized hospital admissions due to complications arising from respiratory and urinary infections of the assisted patients. Strategies should be addressed to reduce unnecessary antibiotic prescribing in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The studies in which multiple infection types were explored simultaneously generally reported conflicting findings. Some studies indicated that antibiotic prescribing in primary care was associated with a reduction or no increase in hospitalisation [22,31], whereas one study reported higher rates of hospitalisation [18], and yet another reported no association between antibiotic prescribing in primary care and antibiotic resistance [30]. It is unlikely that the examination of multiple infection types explains these different findings, given that most of the studies focussed only on RTIs and UTIs [18,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies in which multiple infection types were explored simultaneously generally reported conflicting findings. Some studies indicated that antibiotic prescribing in primary care was associated with a reduction or no increase in hospitalisation [22,31], whereas one study reported higher rates of hospitalisation [18], and yet another reported no association between antibiotic prescribing in primary care and antibiotic resistance [30]. It is unlikely that the examination of multiple infection types explains these different findings, given that most of the studies focussed only on RTIs and UTIs [18,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that antibiotic prescribing in primary care was associated with a reduction or no increase in hospitalisation [22,31], whereas one study reported higher rates of hospitalisation [18], and yet another reported no association between antibiotic prescribing in primary care and antibiotic resistance [30]. It is unlikely that the examination of multiple infection types explains these different findings, given that most of the studies focussed only on RTIs and UTIs [18,30,31]. However, different study designs were adopted such that the target population of the Urrusuno et al study was GPs, whereas other studies focussed on large representative samples of patients using administrative data [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease-specific QIs cannot be applied to this type of data, and therefore, drug-specific QIs are more frequently used. [ 23 , 27–30 , 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…The dandelion is a well‐known herb that is commonly used in traditional Chinese herbal medicine, and its leaves have multiple functions, including reducing swelling, and ameliorating inflammatory diseases 8,9 . Its functions of “clearing heat‐toxins” and “detumescence” are used in the treatment of upper respiratory and urinary tract infections 10 . A recent study showed that liquid dandelion root extract is efficacious against lipopolysaccharide‐induced inflammation in acute lung lesions.…”
Section: Introductionmentioning
confidence: 99%